THE INTELLECTUAL DISABILITY OF THE MAIN CHARACTER AND ITS EDUCATIONAL VALUES OF THE FORREST GUMP MOVIE - Windi Astuti; Hazairin Eko Prasetyo (JELLT (Journal of English Language and Language Teaching), 2020)
The present study aims to find out and describe the educational values reflected in the main character suffering from intellectual disability in Forrest Gump movie and to find out how the intellectual disability influenced the behaviour of the main character in Forrest gump movie. The writer used descriptive qualitative method. The data were in the form of words and sentences. This study was as a qualitative research in which the data were collected from primary and secondary sources. The primary source was the movie itself and its script. The secondary sources were articles, and several references on literature. After the data had been collected the writer used suitable scenes and conversations to analyze the types of educational values in the story. The results reveal that 1) The educational values reflected through the main character were bravery, peace, confidence and potential, loyalty and trustworthiness, respect, love and affection, unselfishness, kindness and friendliness, fairness and humanistic attitudeÂ  2) The intellectual disability affected the behavior of the main character including â€œdifficult to understand some thingsâ€, â€œless able to make decisionâ€, and â€œmake him unaware with some situationsâ€.